(untitled) (Marketing Journal, 2025)
The article presents methodological approaches to assessing and ensuring the economic sustainability of Uzbekistan's cotton -textile clusters. Factors influencing the level of sustainability are identified, and an integrated index for comprehensive assessment is proposed, incorporating financial, production, innovation, labor, environmental, and informational components. Based on the conducted analysis, a trend of growth in the overall economic sustainability indicator of the cluster in the Fergana region during 2020 –2025 was revealed. A methodology for comprehensive diagnostics of sustainability using systemic and multi -level approaches has been developed. The paper provides practical recommendations for strengthening the financial, institutional, production, and environmental sustainability of clusters. The results have both theoretical and practical significance for the development of effective management tools for industrial clusters.